Analysis of Information Security Aspects of Patient Data in Electronic Medical Records at Kebonjati Hospital - Muthiara Putri, Nadya; Setiatin, Sali (International Journal of Psychology and Health Science, 2025)
The development of information technology in the healthcare sector has driven the implementation of Electronic Medical Records (EMR) systems, which play a crucial role in the efficient and effective management of patient data. However, information security in these systems remains a major challenge, given the high sensitivity of patient data and the need to maintain confidentiality. This study aims to analyze the information security aspects of patient data in the Hospital Management Information System at Kebonjati Hospital. A descriptive qualitative approach was used, with data collected through semi-structured interviews with three hospital registration officers. The results indicate that SIMRS already implements user authentication and access control, but significant weaknesses exist, such as the lack of an auto-logout feature, a weak audit trail mechanism, and data validation and integrity issues. Furthermore, IT infrastructure constraints and a lack of staff training also impact patient data security. Based on these findings, it is recommended that the hospital update its system, enhance information security training, and adopt security policies based on international standards such as ISO 27001. Implementing these measures is expected to strengthen patient data security and improve the quality of healthcare services at Kebonjati Hospital.